Peter in early Christianity - Bond, Helen K. (Helen Katharine); Hurtado, Larry W., 1943-2019 (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2015)
Long overshadowed by the apostle Paul, Peter has received increased scholarly attention of late. Building on that resurgence of interest, nineteen internationally prominent scholars of early Christian history examine and reassess the historical Peter and his significance in Christian texts from the first three centuries. Giving due attention to archaeological data and recent scholarship, the contributors offer a comprehensive view of Peter through analysis of both New Testament texts and later, noncanonical literature. Markus Bockmuehl concludes the volume by considering present-day questions about the role of Peter, popes, and church leadership.
The apostle Peter in Protestant scholarship : Cullmann, Hengel, and Bockmuehl / Larry W. Hurtado -- The fisherman from Bethsaida / Sean Freyne -- From Shimon to Petros : Petrine nomenclature in the light of contemporary onomastic practices / Margaret H. Williams -- Was Peter behind Mark's gospel? / Helen K. Bond -- Did Peter really say that? : revisiting the Petrine speeches in Acts / Jonathan W. Lo -- "Another shall gird thee" : probative evidence for the death of Peter / Timothy D. Barnes -- Reassessing Peter's imperception in synoptic tradition / John R. Markley -- The centrality of discipleship in the Johannine portrayal of Peter / Jason S. Sturdevant -- Moving the people to repentance : Peter in Luke-Acts / Finn Damgaard -- The tradition of Peter's literacy : Acts, 1 Peter, and Petrine literature / Sean A. Adams -- Why are there some Petrine epistles rather than none? / Matthew V. Novenson -- Images of Peter in the apostolic fathers / Todd D. Still -- Peter in Paul's churches : the early reception of Peter in 1 Clement and in Polycarp's Philippians / Paul A. Hartog -- On the trail of the scribal Peter : Petrine memory, Hellenist mission, and the parting of the ways in Peter's Preaching / William Rutherford -- "Gnostic" perspectives on Peter / Tobias Nicklas -- Peter in noncanonical traditions / Paul Foster -- When did Peter become bishop of Antioch? / Paul Parvis -- Traces of Peter veneration in Roman archaeology / Peter Lampe -- Scripture's pope meets Von Balthasar's Peter / Markus Bockmuehl.
Includes bibliographical references and indexes.
Includes bibliographical references and indexes.
Keywords: Peter, -- the Apostle, Saint; Church history -- Primitive and early church, ca. 30-600.